Faculty learning processes: A model for moving from scholarly teaching to the Scholarship of Teaching and Learning - Gayle, Barbara M.; Randall, Nancy; Langley, Lin; Preiss, Raymond (Teaching and Learning Inquiry, 2013)
This essay explores the development and conceptual validation of the Faculty Processing Model for SoTL through anecdotal reports gathered from six institutions and additional survey data collected from three institutions. The results identified how faculty learning occurred through faculty development activities across various campuses and how that faculty learning cumulatively represented distinctive developmental stages that led to both cognitive and affective transformations for the professors’ and their students’ learning. This analysis provided a first step in understanding the efficacy of faculty development activities in relation to their impact on student and faculty learning and upon practicing the Scholarship of Teaching and Learning.